Hyperbaric oxygenation in transplantology - O. A. Levina; A. K. Evseev; M. Sh. Khubutiya; A. V. Babkina; A. K. Shabanov (Трансплантология (Москва))
The ability to eliminate any form of oxygen debt by transporting oxygen to organs and tissues, by dissolving it in body fluids, brings hyperbaric oxygenation to a new level of application in transplantology. The review discusses the pathophysiological aspects of hyperbaric oxygenation during ischemia and reinfusion, especially when used in transplantology, and also investigations on the use of hyperbaric oxygenation in model experiments and in clinical practice. Analysis of the efficacy of hyperbaric oxygenation therapy at various stages of the transplantation process (preconditioning, donation, organ storage, in the early and late post-transplant periods) allows us to conclude that this method should be more widely involved in transplantation practice.Authors declare no conflict of interest.